Nurse-to-nurse collaboration between hospital and primary health care on older people’s nursing care – Model, instrument and results - Lemetti, Terhi (fi=Turun yliopisto|en=University of Turku|, 2020)
The purpose of this three-phase study was to develop and preliminary test a hypothetical model of the nurse-to-nurse collaboration between hospital and primary health care on older people’s nursing care and to develop an instrument for the measurement of this collaboration. The ultimate goal was to provide a framework for collaboration in future development to ensure safe and high-quality continuity of care between organisations for older people. Phase I, a descriptive design with a literature review (n=22) and interviews with hospital and primary health care nurses (n=28) and older people (n=18) cared for in both organizations was conducted to develop a hypothetical model to define nurseto- nurse collaboration between hospital and primary health care. In phase II, a descriptive and explorative study design with expert panels (n=10, n=11) and a pilot survey (N=255, n=103, response rate 40.4%) were used to develop and test an instrument, based on the developed model. Finally, in phase III, a descriptive and cross-sectional study design with survey study (N=1435, n=443, response rate 30.9%) was used to assess the level of nurse-to-nurse collaboration between hospital and primary health care on older people’s nursing care in Finland and to evaluate the theoretical structure of developed model and the psychometric properties of the developed instrument. The data analysis methods used in this study were content analysis, dimensional analysis, descriptive and inferential statistics. In this study, the hypothetical model and instrument were developed with four dimensions: Context and Situation, Conditions, Processes and Interactions, and Consequences. The developed model demonstrated a partly favourable structure and the developed instrument demonstrated preliminary and acceptable psychometric properties. The results indicated that there is nurse-to-nurse collaboration and it is important; the collaboration includes respect and confidential interaction from the perspective of hospital and primary health care nurses. In the further development, the commonly agreed practices, objectives and responsibilities, and nurses’ roles will need to be defined more clearly in this collaboration. In addition, there is a need for structures and support from organisations and society to develop collaboration.

Erikoissairaanhoidon ja perusterveydenhuollon sairaanhoitajien välinen yhteistyö ikääntyvän potilaan hoidossa – Malli, mittari ja tulokset Tämän kolmivaiheisen tutkimuksen tarkoituksena oli kehittää ja alustavasti testata hypoteettinen malli erikoissairaanhoidon ja perusterveydenhuollon sairaanhoitajien väliseen yhteistyöhön ikääntyvän potilaan hoidossa sekä kehittää mittari tämän yhteistyön toteutumisen mittaamiseen. Tavoitteena oli tuottaa viitekehys yhteistyölle sen tulevaa kehittämistä varten varmistamaan ikääntyvän potilaan hoidon jatkuvuutta turvallisesti ja laadukkaasti organisaatioiden välillä. Ensimmäisessä vaiheessa tutkimus toteutettiin kuvailevalla tutkimusasetelmalla, jossa kehitettiin hypoteettinen malli sairaanhoitajien yhteistyöhön erikoissairaanhoidon ja perusterveydenhuollon välillä kirjallisuuskatsauksen (n=22), erikoissairaanhoidon ja perusterveydenhuollon sairaanhoitajien (n=28) sekä molemmissa organisaatioissa hoitoa saavien ikääntyvien potilaiden (n=18) haastattelujen avulla. Toisessa vaiheessa kuvailevalla ja eksploratiivisella tutkimusasetelmalla asiantuntijapaneelien (n=10, n=11) ja pilottikyselytutkimuksen (N=255, n=103, vastausprosentti 40.4 %) avulla kehitettiin ja testattiin malliin pohjautuva mittari. Kolmannessa vaiheessa kuvailevalla poikkileikkaustutkimusasetelmalla ja kyselytutkimuksen (N=1435, n=443, vastausprosentti 30.9 %) avulla mitattiin erikoissairaanhoidon ja perusterveydenhuollon sairaanhoitajien välisen yhteistyön toteutumista Suomessa ikääntyvän potilaan hoidossa sekä arvioitiin mallin teoreettista rakennetta ja mittarin luotettavuutta. Aineisto analysoitiin sisällönanalyysilla, dimensioanalyysillä ja tilastoanalyyseillä. Tässä tutkimuksessa kehitettiin hypoteettinen malli ja mittari, jotka sisältävät neljä dimensiota: Konteksti ja Tilanne, Olosuhteet, Prosessit ja Vuorovaikutukset sekä Seuraukset. Malli osoitti osittain toimivaa rakennetta ja mittari osoitti alustavaa sekä hyväksyttävää luotettavuutta. Tulokset osoittivat, että erikoissairaanhoidon ja perusterveydenhuollon sairaanhoitajien näkökulmasta heidän välillä on tärkeää yhteistyötä, joka sisältää kunnioittavaa ja luottamuksellista vuorovaikutusta. Yhteisesti sovitut toimintatavat, tavoitteet ja vastuut sekä sairaanhoitajien roolit tulee kuitenkin määritellä selkeämmin yhteistyötä kehittäessä. Yhteistyön toteutuminen vaatii rakenteita ja tukea organisaatioilta sekä yhteiskunnalta.